Legal Implications of The Notary’s Position in Relation to Conflict of Interest Involving Client - Kamila, Amalia; Rasji, Rasji (Universitas Islam Sultan Agung, 2025)
This research aims to analyze the legal implications for Notaries who draft deeds for the benefit of clients but contain conflicts of interest that violate the law and the notarial code of ethics, as well as the role of the Regional Supervisory Council (in overseeing such violations. Conflicts of interest in notarial practice may arise when a Notary has personal, financial, or professional ties with one of the parties, thereby compromising neutrality and threatening the validity of the authentic deed. The results of the study indicate that the legal implications include the legal nullification of the deed, the imposition of administrative sanctions such as written warnings, temporary suspension, and even permanent dismissal, as well as potential criminal liability if there is evidence of intent or bad faith. These provisions are regulated under the Notary Law (UUJN), the Notarial Code of Ethics, and relevant provisions of civil and criminal law. In certain cases, deeds executed without the presence of the parties or outside the notary's office without lawful justification are declared legally defective and lose their authenticity. In this context, the Regional Supervisory Council plays a crucial role as a supervisory body authorized to conduct clarification, investigation, and recommend sanctions for Notaries proven to have committed violations. Pursuant to Article 70 of the UUJN, the Regional Supervisory Council is also empowered to receive public complaints and prevent violations through periodic evaluations. Thus, the Regional Supervisory Council serves as an essential instrument in upholding the integrity of the notarial profession and maintaining public trust in authentic deeds as valid legal evidence.